Perencanaan Komponen Dies Pipa PVC Jenis SNI-10 dengan Computer Aided Design and Drafting - Lydia Anggraini; Tirta Kumala (Journal of Mechanical Engineering and Mechatronics, 2016)
Abstract. In the manufacturing industry, the machine components are not only able to process metallic materials but also other materials such as polymers, ceramics, and composites. Although, the PVC pipe is one of the many common types of polymers. This is because, the PVC pipe has several advantages such as light weight, high corrosion resistance, easy to install, and more economic. The process of creating an application program of machine elements for the manufacture of dies on a PVC pipe, the process parameters need to be planned well. Therefore, the analysis of these calculations is made to be used as an input data in program design elements of the planning application machines for the manufacture of dies on PVC pipe. This program uses a Computer Aided Design and Drafting (CADD) that use AutoLISP program for the imaging process and planning and also Dialogue Control Language to do the selection process, from materials selection to the calculation until the image as required to be produced. An expected program designing application machine elements for the manufacture of dies on PVC pipe can be applied to improve the previous method which is time consuming and the accuracy of the imaging process.Keywords. Designing, Drawing, Computer Aided Design and Drafting, PVC Pipe, AutoLISP.